2015
DOI: 10.1186/s13104-015-1590-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and overweight and associated factors among financial institution workers in Accra Metropolis, Ghana: a cross sectional study

Abstract: BackgroundCertain professions are associated with low physical activity. Workers in such professions spend the most part of their adult working lives less engaged in physical activity if they don’t consciously exercise outside of working hours. This increases their risk of obesity and its associated diseases. This study determined the prevalence of obesity and overweight and associated factors among workers of a financial institution in Accra Metropolis, Ghana.MethodsA cross-sectional study was conducted among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
52
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 48 publications
13
52
3
3
Order By: Relevance
“…This finding is consistent with several other studies in Nigeria 8,9 and other African countries. 26,27 This, however, is contrary to the report from most high-income countries 28,29 where male gender was reported to be associated with obesity. Several reasons have been proffered as being responsible for the higher prevalence of obesity found among females.…”
Section: Discussionmentioning
confidence: 63%
“…This finding is consistent with several other studies in Nigeria 8,9 and other African countries. 26,27 This, however, is contrary to the report from most high-income countries 28,29 where male gender was reported to be associated with obesity. Several reasons have been proffered as being responsible for the higher prevalence of obesity found among females.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, a population survey among 1,521 Nigerian adults found overweight and obesity rates of 32.2% and 19.6% for men and 29.8% and 36% for women respectively [11]. Data from Ghana among financial institution workers showed over half of participants were either overweight (37.8%) or obese (17.8%), with physical inactivity, being married, female gender and increasing age being independently associated with increased body mass [12]. In Cameroon, Fezeu et al showed an almost doubling of the age-standardized prevalence of overweight and obesity in rural settings between 1994 and 2003 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Office workers have high-risk of overnutrition (overweight and obesity) as one of the risk factors of hypertension because of the higher rate of sit hours and long working hours in the workplace. In most cases, workers had long sitting hours as much as 3 hours/day in average and higher sitting hours related to higher BMI (3,13,14). Beside of BMI, the other indicators of over nutrition that was related to hypertension were waist circumference, waist to hip ratio (WHR), waist to height ratio (WHtR), and body composition such as total body fat (TBF) and visceral fat (VF)) (6-9).…”
Section: Discussionmentioning
confidence: 99%